Bio-Inspired Ionic Sensors: Transforming Natural Mechanisms into Sensory Technologies - Choi, Kyongtae; Lee, Gibeom; Lee, Min‑Gyu; Hwang, Hee Jae; Lee, Kibeom; Lee, Younghoon (Nano-Micro Letters, 2025)
Many natural organisms have evolved unique sensory systems over millions of years that have allowed them to detect various changes in their surrounding environments. Sensory systems feature numerous receptors—such as photoreceptors, mechanoreceptors, and chemoreceptors—that detect various types of external stimuli, including light, pressure, vibration, sound, and chemical substances. These stimuli are converted into electrochemical signals, which are transmitted to the brain to produce the sensations of sight, touch, hearing, taste, and smell. Inspired by the biological principles of sensory systems, recent advancements in electronics have led to a wide range of applications in artificial sensors. In the current review, we highlight recent developments in artificial sensors inspired by biological sensory systems utilizing soft ionic materials. The versatile characteristics of these ionic materials are introduced while focusing on their mechanical and electrical properties. The features and working principles of natural and artificial sensing systems are investigated in terms of six categories: vision, tactile, hearing, gustatory, olfactory, and proximity sensing. Lastly, we explore several challenges that must be overcome while outlining future research directions in the field of soft ionic sensors. Highlights: 1 This review provides an overview of recent developments in soft ionic sensors inspired by biological sensory systems, focusing on their material properties and working principles. 2 The features and working principles of natural and artificial sensing systems are investigated in terms of six categories: vision, tactile, auditory, gustatory, olfactory, and proximity sensing. 3 The challenges encountered in developing soft ionic sensors and the future research directions to overcome these issues are discussed.